Negotiation of State and Customary Authority over Village Governance in Jayapura Regency - Faisal; Lukman Ansar; Tarmizi; Dandi Wahyudin; Andi Sugirman (Al-Bayyinah, 2026)
This study aims to examine the dynamics of authority negotiations between state authorities and customary institutions in the administration of village governance in Jayapura Regency. Normatively, the existence of customary law communities is constitutionally guaranteed through Article 18B of the 1945 Constitution, which was further strengthened in Law Number 21 of 2001 concerning Special Autonomy for Papua. Using qualitative methods with a socio-legal approach, this study found that the Jayapura Regency Government, through Regional Regulation Number 8 of 2016, has taken progressive steps by integrating customary leadership structures into the formal administrative system through the Customary Village (Kampung Adat) scheme. The research findings indicate a dual power structure, in which Ondoafi performs roles encompassing governance, norm formation, and dispute resolution based on charismatic legitimacy that intersects with the demands of modern bureaucracy. The authority negotiation process is intense, particularly in the context of customary land (ulayat) management and conflict resolution through the Para-Para Adat mechanism, which, in practice, is considered more effective in maintaining social cohesion than formal judicial mechanisms. However, this integration still faces various obstacles, particularly the tension between state administrative standards and the genealogical and communal nature of traditional leadership. In conclusion, strengthening the position of Ondoafi as a liaison between investment interests and the protection of customary rights is a key factor in the successful implementation of special autonomy, while remaining within a framework of public accountability and respect for human rights principles.